Välkommen : förslag till ny stadspark i Göteborg - Eriksson, Louise (SLU/Dept. of Urban and Rural Development, 2006)
The landscape is a great asset for Göteborg as a city and places in the landscape are much used by the public. This diploma work deals with the question of how nature in Göteborg can become more accessible and how a place in it can be supplemented with new landscape elements. It is a proposal for a new urban park at Björlanda peninsula in the western part of Hisingen, Göteborg, which today belongs to the Swedish Armed Forces and is a part of the Nature-2000 area "Nordre älvs estuarium". The reason for choosing this place is that it is the only area around the costal area in Göteborg that has not been built on and that it contains a very varied landscape.